2019
DOI: 10.14710/rotasi.20.4.249-257
|View full text |Cite
|
Sign up to set email alerts
|

Application of Polishing AISI 316L Stainless Steel Ball Bearing with A Magnetic Abrasive Finishing Process: A Review

Abstract: Advanced machining process telah terbukti dalam teknologi proses rekayasa untuk surface finishing dan proses material removal, atau dengan proses traditional finishing: fase fundamental, unrestrained, dan permintaan tinggi dalam fase tenaga kerja selama produksi. Finishing abrasif magnetik, pada polishing dalam proses non-konvensional mampu menyelesaikan dengan presisi dengan proses pemesinan yang dikontrol oleh medan magnet dan itu tidak berlaku untuk beberapa proses kompleks di mana teknik penyelesaian konve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They reported that the polishability of the surface parallel to build direction was higher than the transverse surface. Munyensanga et al [17] reviewed the application of MAM to polish AISI 316L stainless steel ball-bearing. They reported that a minimum Ra of 0.077 µm was achieved at optimal finishing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the polishability of the surface parallel to build direction was higher than the transverse surface. Munyensanga et al [17] reviewed the application of MAM to polish AISI 316L stainless steel ball-bearing. They reported that a minimum Ra of 0.077 µm was achieved at optimal finishing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [37] reported that the surface parallels to build direction had greater polishability in comparison to the transverse surface in the polishing of 316L stainless steel with G50 steel grits μm as the abrasives. Munyensanga et al [38] polished AISI 316L stainless steel ball-bearing by MAAF process. The authors stated that the MAAF process yielded a minimum Ra of 0.0766 μm at the optimal processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…8 The atomizing rapid solidification magnetic abrasives developed by the research group have a large number of static effective cutting edges, exhibiting excellent performance. The abrasive particles are evenly distributed on the iron matrix, which makes the magnetic abrasives have good grinding performance when grinding all kinds of ceramic, 316 Stainless steel, 9 Ti6Al4V, Inconel 718, 10,11 cast iron materials, 12 organic glass, and metal materials. Compared with the magnetic abrasives prepared by the sintering method, the chemical composition of atomized powder particles is the same and uniform, and does not exist segregation phenomenon.…”
Section: Brief Introduction Of Atomizing Rapid Solidification Magnetic Abrasivementioning
confidence: 99%